FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMSI IKAN ANAK USIA SEKOLAH (STUDI KASUS: SISWA SMPN 1 ASTAMBUL KABUPATEN BANJAR) - Muhammad Busairi; Emmy Sri Mahreda; Leila Ariyani Sofia (Universitas Lambung Mangkurat, 2022)
Fish consumption is one of the factors that directly affect the nutritional status of a person, family, or community. State Junior High School Astambul 1, Astambul District, Banjar Regency, has several canteens that sell a variety of foods. Most of the students prefer fried chicken over some other fish dishes. Therefore, this study aims to analyze the factors that influence fish consumption preferences in school-age children. This study uses primary data and secondary data. Primary data were collected through surveys, observations, and direct interviews with respondents with the help of a questionnaire. Data analysis used: (1) Instrument Test (validity test and reliability test), (2) Logistics analysis (Hosmer and Lemesho's Goodness, Omnibus Tests, Nagelkerke R Square, Correlation Matrix and Wald's Test). The results of the analysis show that 1) The regression coefficient (β) of the social status variable is 2.283 and the significance value = 0.019 (p < 5%). 2) The value of the regression coefficient (β) of the mother's education variable is 2.458 and the significance value = 0.017 (p < 5%). 3). The value of the regression coefficient (β) of the energy adequacy level variable is 0.004 and the significance value = 0.05 (p < 5%). 4) The regression coefficient (β) of the infection variable is 14,292 and the significance value = 0.05 (p > 5%). 5) The regression coefficient (β) of the infection variable is 19.098 and the significance value = 0.05 (p > 5%). The conclusion of the analysis is that socioeconomic status, mother's education, and energy adequacy level have a significant effect on fish consumption, while infection and child nutritional status have no significant effect on fish consumption.